GROUNDWATER OCCURRENCE ON JEJU ISLAND, KOREA - Won J.; Lee J.; Kim J.; Koh G. (My University, 2006)
Jeju Island is a volcanic island composed predominantly of permeable basalts. The island is poor in surface water but abundant in groundwater. No actual perennial streams exist and the water resources on the island are dependent almost entirely on groundwater. The groundwater bodies on the island are classified into three general categories: high level, basal and parabasal groundwaters. The parabasal groundwater is further subdivided into lower and upper parabasal groundwaters due to the position of the Seogwipo Formation, which is made up of sedimentary rocks with a low permeability. The distribution of each groundwater type was evaluated through analyses of the spatial distribution of the Seogwipo Formation and the hydraulic gradient of the groundwater. Basal groundwater emerges extensively along the coast of the eastern sector, less commonly along the coast of the western sector. Parabasal groundwater occurs extensively over most of the island except for the southern sector, where it occurs only locally in the coastal area. This paper presents a summary of several studies on the occurrence and features of groundwater resources on Jeju Island, the largest island in Korea.
Keywords: JEJU ISLAND; SEOGWIPO FORMATION; HIGH LEVEL GROUNDWATER; BASAL GROUNDWATER; PARABASAL GROUNDWATER; KOREA